Trends, impact and the challenge of technology in higher learning institutions - Habulan, Nenita V. (Tanglaw: official journal of the College of Education, 2003)
There seems to be no limit to what technology can do and is capable of doing in transforming our lives now and in the future. And in the context of technological innovations, that future is already happening now. IT scholars and expert continue to discover, develop, and explore the many other areas where technology can simplify, if not totally replace, the human function. Practically, there is no segment in society today that is not infiltrated, mediated, or dominated by technology. And education is no exemption. This paper attempts to present the trends, impact and the challenge of technology in higher learning institutions as they try to survive and become relevant in this highly technological and competitive global society.